Analisis Pengaruh Kualitas Sistem Informasi Akuntansi Terhadap Penerimaan Teknologi Di Sektor UKM Medan Dengan Pendekatan Model TAM - Dina Indah Permatasari; Eni Duwita Sigalingging (Universitas Pendidikan Ganesha, 2022)
The purpose of this study was to analyze the effect of taxpayer awareness, public services, and tax sanctions on motor vehicle taxpayer compliance at the UPT office. SAMSAT Karo Regency, To find out whether tax knowledge can moderate the relationship between taxpayer awareness, public services, and tax sanctions on motor vehicle taxpayer compliance at the UPT office. SAMSAT Karo Regency. This research belongs to the type of causality research, namely to examine the causal relationship between taxpayer awareness, public services and tax sanctions, which is moderated by tax knowledge. This type of research data is primary data because it is carried out by means of field studies by distributing questionnaires. The data analysis technique used in this study is using SPSS Version 22.The results showed thattaxpayer awareness, public services, and tax sanctions positive and significant to motor vehicle tax compliance at the UPT office. SAMSAT Karo Regency.Tax knowledgecan moderate the relationship between taxpayer awareness, public services, and tax sanctions on motor vehicle taxpayer compliance at the UPT office. Karo District SAMSAT